2005
DOI: 10.1021/jp040718r
|View full text |Cite
|
Sign up to set email alerts
|

Identification, Structure, and Spectroscopy of Neutral Vanadium Oxide Clusters

Abstract: Neutral vanadium oxide clusters are studied by photoionization time-of-flight (TOF) mass spectroscopy, electronic spectroscopy, and density functional theory (DFT) calculations. Mass spectra of vanadium oxide clusters are observed by photoionization with lasers of three different wavelengths: 118, 193, and 355 nm. Mechanisms of 118 nm single photon ionization and 193 and 355 nm multiphoton ionization/fragmentation of vanadium oxide clusters are discussed on the basis of observed mass spectral patterns and line… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

6
99
0
1

Year Published

2006
2006
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 98 publications
(106 citation statements)
references
References 65 publications
6
99
0
1
Order By: Relevance
“…The investigation of gas-phase cluster reactivity both from experimental and theoretical points of view has proven to bring valuable information on the elementary steps involved. Gas-phase clusters can be easily obtained and analyzed in neutral, 1 cationic, 2 and anionic forms, [3][4][5] and they serve as excellent models for complex catalytic systems. 6,7 In this work, we use a vanadia cluster to determine the catalytic mechanism of methanol oxidation in hydrated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of gas-phase cluster reactivity both from experimental and theoretical points of view has proven to bring valuable information on the elementary steps involved. Gas-phase clusters can be easily obtained and analyzed in neutral, 1 cationic, 2 and anionic forms, [3][4][5] and they serve as excellent models for complex catalytic systems. 6,7 In this work, we use a vanadia cluster to determine the catalytic mechanism of methanol oxidation in hydrated conditions.…”
Section: Introductionmentioning
confidence: 99%
“…In general, single photon ionization is a good way to study van der Waals and hydrogen bonded clusters since less fragmentation of the parent cluster ions occurs compared to EI and MPI. We have previously demonstrated that, if 10.5 eV is sufficient energy for the ionization of a cluster, 37,38 a 118 nm vuv laser provides a nonresonant soft ionization for metal oxide and methanol clusters, 37,38 as fragmentation is minimized during the ionization process. The 10.5 eV photon, however, is not energetic enough to meet the VIE of ͑H 2 O͒ n .…”
Section: Introductionmentioning
confidence: 99%
“…Two predominant components, that is, Ti n O 2n-2 and Ti n O 2n-1 , were indicated in the spectrometry and the former exhibits larger correlated fluctuations. [13] In contrast, main products in the single-photon ionization experiment were predicted to be the Ti n O 2n and Ti n O 2nþ1 clusters by Matsuda and Bernstein [14] Nevertheless, both studies suggested that the cluster growth process is predominated by addition of TiO 2 species. [13,14] Helden et al applied infrared resonance enhanced multiphoton ionization to study the titanium oxide in the gas phase.…”
Section: Introductionmentioning
confidence: 99%